Temperature‐dependent irreversible conformational change of recombinant ADAMTS13 upon metal ion chelation. (21st April 2019) - Rottensteiner, Hanspeter; Kaufmann, Stefan; Rathgeb, Anna; Kink, Barbara; Plaimauer, Barbara; Matthiessen, Peter; Hann, Stephan; Scheiflinger, Friedrich
Abstract: Background: The catalytic domain of ADAMTS13 possesses one Zn 2+ and up to three putative Ca 2+ binding sites and can be inactivated by chelating agents. Although replenishment with an appropriate metallic cation is thought to restore the enzyme's proteolytic activity fully, ADAMTS13 stability in a metal ion‐depleting environment has not been explored. Objectives: To address the stability of ADAMTS13 in citrated human plasma. Methods: ADAMTS13 activity was measured using the FRETS‐VWF73 fluorogenic assay. The molar ratio of metals bound to ADAMTS13 was determined by size exclusion chromatography inductively coupled plasma mass spectrometry (SEC‐ICP‐MS). Higher‐order structural changes were analyzed using Fourier‐transformed infrared spectroscopy and dynamic light scattering. Results: ADAMTS13 was stable at room temperature for up to 24 hours irrespective of the presence of citrate (0.38%). However, at 37°C, citrate caused a time‐dependent activity decrease. No ADAMTS13 activity decrease was seen in heparinized plasma, but the addition of citrate again caused ADAMTS13 instability at 37°C. Scavenging of citrate by the addition of Ca 2+ or Zn 2+ prior to but not postincubation prevented the activity decrease of the enzyme. The SEC‐ICP‐MS analyses showed that ADAMTS13 only bound Zn 2+ and that its reduced activity correlated with a gradual loss of bound Zn 2+ . Concomitant higher‐order structural analyses demonstrated structural changes in ADAMTS13 that are typical of less‐ordered protein structures. Conclusions: Zn 2+ is required to stabilize ADAMTS13 structure at physiologic temperature, thereby preventing irreversible loss of enzyme activity. This finding is particularly important to consider when using citrated human plasma as a source of ADAMTS13 in clinical settings.